Low-temperature electron transport in [110] and [100] silicon nanowires: a DFT-Monte Carlo study - Shiri, Daryoush; Nekovei, Reza; Verma, Amit (Frontiers in Nanotechnology, 2024)
The effects of very low temperature on the electron transport in a [110] and [100] axially aligned unstrained silicon nanowires (SiNWs) are investigated. A combination of semi-empirical 10-orbital tight-binding method, density functional theory (DFT), and Ensemble Monte Carlo (EMC) methods are used. Both acoustic and optical phonons are included in the electron-phonon scattering rate calculations covering both intra-subband and inter-subband events. A comparison with room temperature (300 K) characteristics shows that for both nanowires, the average electron steady-state drift velocity increases at least 2 times at relatively moderate electric fields and lower temperatures. Furthermore, the average drift velocity in [110] nanowires is 50 percent more than that of [100] nanowires, explained by the difference in their conduction subband effective mass. Transient average electron velocity suggests that there is a pronounced streaming electron motion at low temperature which is attributed to the reduced electron-phonon scattering rates.